Analysis of Wake Turbulence for a Savonius Turbine for Malaysia’s Slow-Moving Current Flow - Anas Abdul Rahman; Kumaran Rajendran; Ayu Abdul-Rahman; Gisrina Elin Suhri; Lakshuman Dass (International Journal of Renewable Energy Development, 2022)
With Malaysia being surrounded by water bodies, tidal energy could be used for energy extraction. While several turbine designs and technologies have been used for tidal energy extraction, information on the use of vertical-axis tidal turbines (VATTs) for shallow-water applications is scarce. However, implementing horizontal-axis tidal turbines (HATTs) is not feasible due to Malaysian ocean depths. Hence, examining the wake-flow characteristics of VATTs in a shallow water-working environment in Malaysia is essential. The wake turbulence of the Savonius turbine model was compared with that of a hypothetical ‘actuator' cylinder, a VATT representation. Subsequently, the wake turbulences of a Savonius turbine model in static and dynamic simulations were compared to understand the flow distinction. Compared with that exhibited by the hypothetical actuator cylinder of 2.5 m, the hypothetical actuator cylinder of 5 m exhibits greater velocity deceleration. Additionally, the modelled Savonius turbine exhibits significantly more deceleration than that exhibited by the hypothetical actuator cylinder. Finally, the analysis of the static model of the Savonius turbine shows deceleration that is greater than that of the dynamic model.